Effect of Work Stress toward Organizational Commitment Mediated By Knowledge Regarding Covid-19 & Work Satisfaction during Covid-19 in Tabanan Hospital - Levina, Analia; Temaluru, Yohanes; Wiradana, A.A.N. Putra (Budapest International Research and Critics University, 2022)
Human resources (HR) are the most important part of an organization because they are the ones who move and develop the organization with the goals of the organization. The purpose of this study is to analyze the effect of work stress on work commitments mediated by job satisfaction and knowledge about Covid-19 during the Pandemic Covid-19 at Tabanan Bali Regional Hospital. Testing the research model of modification results from previous research was carried out by a quantitative survey method with a cross-sectional data approach. Respondents' data were taken purposive sampling with questionnaires from individuals who work in Tabanan Hospital and interact directly with Covid-19 patients, and are more than 18 years old. There are 85 samples that meet the requirements and analyzed with SPSS, and the results obtained that 1) Work stress and work satisfaction are affecting organizational commitment, 2) Job satisfaction is affecting work stress, 3) Covid-19 knowledge among healthcare workers neither affecting organizational commitment nor work stress, 4) Job satisfaction and Covid-19 knowledge do not mediate between work stress and organizational commitment.